Rasionalitas dalam Penafsiran: : Analisis Kritis terhadap Kitab Tafsīr Al-Mīzān karya Allāmah Al-Ṭabāṭabāʾī - Hakim, Fikri (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2024)
This study focuses on analyzing the rationality and modernity in Tafsīr al-Mīzān by Allāmah al-Ṭabāṭabāʾī, a work composed within the Islamic scholarly tradition that has continuously been shaped by sociocultural contexts across different periods. The primary objective of this research is to evaluate the extent to which Tafsīr al-Mīzān can be categorized as a “modern” or “contextual” tafsir, particularly concerning sensitive issues such as usury (riba), marriage, and gender relations. Employing a qualitative approach based on library research, this study examines a wide range of primary and secondary sources, including the Tafsīr al-Mīzān itself, academic books, and relevant scholarly articles. A critical analysis approach is applied to map out the concept of rationality and identify any potential ideological bias within the tafsir. The findings indicate that al-Ṭabāṭabāʾī frequently presents rational arguments and responds to contemporary intellectual challenges—for instance, by rejecting sectarian fanaticism and offering a synthesis between Qur’anic teachings and philosophical reasoning. Nonetheless, Shiite perspectives remain evident in his interpretations, particularly regarding certain subjects like temporary marriage (nikah mut‘ah). Thus, although Tafsīr al-Mīzān provides a rational dimension, its underlying ideological influence remains prominent and sparks debate concerning its “modern” and “contextual” claims. These findings imply the need to reassess the boundaries of rationality in Qur’anic exegesis and the role of mazhab-based context in the interpretive process.